Verbascoside Protects Gingival Cells against High Glucose-Induced Oxidative Stress via PKC/HMGB1/RAGE/NFκB Pathway - Pei-Fang Hsieh; Cheng-Chia Yu; Pei-Ming Chu; Pei-Ling Hsieh (MDPI AG, 2021)
Impaired wound healing often occurs in patients with diabetes and causes great inconvenience to them. Aside from the presence of prolonged inflammation, the accumulation of oxidative stress is also implicated in the delayed wound healing. In the present study, we tested the effect of verbascoside, a caffeoyl phenylethanoid glycoside, on the improvement of cell viability and wound healing capacity of gingival epithelial cells under high glucose condition. We showed that verbascoside attenuated the high glucose-induced cytotoxicity and impaired healing, which may be associated with the downregulation of oxidative stress. Our results demonstrated that verbascoside increased the activity of the antioxidant enzyme SOD and reduced the oxidative stress indicator, 8-OHdG, as well as apoptosis. Moreover, verbascoside upregulated the PGC1-α and NRF1 expression and promoted mitochondrial biogenesis, which was mediated by suppression of PKC/HMGB1/RAGE/NFκB signaling. Likewise, we showed the inhibitory effect of verbascoside on oxidative stress was via repression of PKC/HMGB1/RAGE/NFκB activation. Also, our data suggested that the PKC-mediated oxidative stress may lead to the elevated production of inflammatory cytokines, IL-6 and IL-1β. Collectively, we demonstrated that verbascoside may be beneficial to ameliorate impaired oral wound healing for diabetic patients.